MAXMUD QAShQARIYDIŃ «DEVONU LUǴATIT TÚRK» MIYNETINDEGI QARAÚYShÍLÍK ATAMALARÍNÍŃ QOLLANÍLÍWÍ - Arzimova, A.S. (ILIM hám JÁMIYET, 2025)
This article explores the use of terminology related to traditional nomadic dwellings in Mahmud al-Kashgari’s work Dīwān Lughāt at-Turk, as well as their appearance within certain proverbs and sayings. The analysis is conducted from a linguocultural perspective, with a focus on the distinctive features of these terms in the modern Karakalpak language. The study holds significant value for the development of contemporary Karakalpak literary language and the research of vocabulary connected to traditional housing.